Pembuatan Video Iklan Produk Kopi Sinar Puntang Menggunakan Aplikasi Adobe Premiere Pro: Studi Kasus Pada Kopi Sinar Puntang - Ashari, Salma; Darsiti (Melati Institute, 2024)
Advertising is one of many promotional strategies that are often used by companies to provide information, invite, and increase the number of buyers or the target public. Currently, the development of television advertising has experienced rapid progress, with telecommunications products becoming the largest sector in advertising expenditure. The large number of service advertisements shown on television is due to the consumer’s need to understand the message conveyed in the advertisements. Advertising attached to the media can influence knowledge abput the brand being promoted. Promotional videos which will be distributed via social media platforms such as Facebook, Instagram, Youtube, have become a popular and needed trend today. The purpose of his research is to create a promotional video that introduces Sinar Puntang Coffee. This multimedia research is carried out by following 6 steps, the first is the concept or drafting which explains the design process, collting materials and making a product or assembly. Testing is the process of testing or trying out an Adobe Premiere Pro product, sydtem or aplications with the aim of determining quality and reliabity.